The role of multinational corporations and corporate governance in facilitating industrial development in Tanzania: A case study of Coca Cola Kwanza Limited. - Mwakasala, Absalom H. (Mzumbe University, 2026)
A dissertation submitted to Dar es Salaam campus college in partial fulfillment of the requirements for the award of degree Master of Business Administration (Corporate Management) of Mzumbe University.